ANALISIS YURIDIS TERHADAP KEWAJIBAN NOTARIS DALAM MELAPORKAN TRANSAKSI KEUANGAN YANG MENCURIGAKAN DALAM REZIM ANTI MONEY LAUNDERING - FLORENSHIA FLORENSHIA (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1.  Prof. Dr. Bismar Nasution, SH, MH2.  Notaris Dr. Suprayitno, SH, MKn3.  Dr. T. Keizerina Devi A, SH, CN, MHum Government Regulation No. 43/2015 includes a Notary as an official whois required to report any suspicious financial transaction; in this case, he has to report all financial transactions of the persons appearing which are allegedly as money laundering. His liability is to keep the confidentiality of the content of the deeds he hasdrawn up and what criteria which are considered being suspicious. The research used juridical empirical and descriptive analytical method by analyzing UUJN (Notarial Act) No. 30/2004 in conjunction with UUJN No. 2/2014, Law No 8/2010 on Prevention and Eradication of Money Laundering Criminal Act and related Supplementary Regulations. Reporting suspicious financial transaction is a good effort in eradicating and preventing money laundering criminal act, especially in Indonesia. In this case, a Notary also lays an important role in eradicating and preventing it. Based on this research, it is found that suspicious financial transaction which has to be designed and reported by a Notary still does not explain clearly and in detail so that he is required to be more careful in doing his profession. The government should provide clear definition about any suspicious financial transaction so that it does not harm informers, especially Notaries.Keywords: Notary, Money Laundering, Criteria of Suspicious Financial Transaction